Meta-analysis: Epstein-Barr Virus genes - EBNAs, LMPs, and EBERs one of the major causes of nasopharyngeal cancer - Nguyễn Hoàng Anh Tuấn; Thiều Hồng Huệ; Lao Đức Thuận; Lê Huyền Ái Thuý (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ, 2019)
Nasopharyngeal cancer is the most common cancer of head and neck cancer in Vietnam. The infection of Epstein-Barr virus (EBV) has been reported to be the cause of nasopharyngeal tumorigenesis. In Vietnam, the studies relevant to EBV, especially the molecular of EBV, are still limited. In the current study, the databases were systematically analyzed to establish the scientific basis for the molecular of EBV which could be applied in further studies. This study was focused on the analysis of three families of EBV genes, included EBNAs, LMPs and EBER based on a meta-analysis. As the result, most studies were focused on the detection of EBNA-1, LMP-1 and EBER. The frequencies of EBNA-1, LMP-1 and EBER were 92.12%; 78.93% and 88.12%, respectively. Moreover, a random effect model was applied to calculate the OR and RR: EBNA-1: RR=20.10; OR= 332.75; LMP-1: RR=3.63; OR=17.9 and EBER: RR=5.4; OR=46.11. Those results indicated that the presence of EBV genes was significantly associated with nasopharyngeal carcinoma. According to the method, PCR was the common method used for the detection of the EBV genes’ presence. Moreover, the nasopharyngeal biopsy was the main source of samples enrolled in nasopharyngeal cancer studied. In summary, we successfully conducted the molecular database about the presence of EBV genes, included the frequency, OR and RR value to be the scientific database for further studies relevant to nasopharyngeal cancer in the Vietnamese population.